A new measure of the intensity of capital account openness - Ling, Tai Hu; Lim, Kian Ping; Cheah, Wai Loon (Universiti Malaysia Sabah, 2013)
It is widely acknowledged that many countries have capital controls that are quite strict on paper but Ineffective in their enforcement, so their actual capital flows are quite high. At the other extreme, many countries are quite open to global capital markets on a de jure basis, but in practice capital flows are minimal. Hence, to capture the degree of capital account openness, it is important to capture both the de jure (legal-based) and de fado (outcome-based) aspects so that its impacts to the economy will not be underestimated. Motivated by these shortcomings, the main objective of this study is to construct a new composite indicator of capital account openness that captures both the de jure and de fado information. This newly constructed index is found positively related to productivity growth both short-run and long-run in the case of Malaysia. The same technique is also used to examine the lucas paradox using dynamic panel GMM analysis for 140 countries. This study also finds that institutional quality is found to be significantly and positively related to capital flows. The new findings are expected to provide some Important implications to the policymakers in considering the innumerable benefits of capital flows.